1989
DOI: 10.1172/jci114382
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a satellite fatty acid ethyl ester synthase from human myocardium as a glutathione S-transferase.

Abstract: Nonoxidative alcohol metabolism catalyzed by fatty acid ethyl ester (FAEE) synthases may contribute to extrahepatic injury resulting from alcohol abuse. Unlike rabbit myocardial FAEE synthase, that from human heart has a satellite minor synthase (I) eluting from DEAE cellulose at a conductivity of 5 mS. Synthase I was purified 1,1 18-fold to homogeneity by sequential gel permeation, hydrophobic interaction, and Superose-12 fast-protein liquid chromatographies. SDS-PAGE showed a single polypeptide with a molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 20 publications
0
21
1
Order By: Relevance
“…Human myocardial FAEE synthase was purified to homogeneity by sequential DEAE-cellulose, gel permeation, hydrophobic interaction, and immunoaffinity chromatographies (1,6). In brief, human heart soluble fraction was applied to a DEAE-cellulose column (5 x 16 cm) in 1 mM 2-mercaptoethanol/10 mM Tris(hydroxymethyl)aminomethane (Tris), pH 8.0.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Human myocardial FAEE synthase was purified to homogeneity by sequential DEAE-cellulose, gel permeation, hydrophobic interaction, and immunoaffinity chromatographies (1,6). In brief, human heart soluble fraction was applied to a DEAE-cellulose column (5 x 16 cm) in 1 mM 2-mercaptoethanol/10 mM Tris(hydroxymethyl)aminomethane (Tris), pH 8.0.…”
Section: Methodsmentioning
confidence: 99%
“…We have purified both a minor (cationic) and a major (anionic) form of FAEE synthase from human myocardium (6). The anionic form of FAEE synthase has a molecular weight of 26,000 and is the counterpart of that from rabbit heart (1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have described the copurification of FAEE synthase and GST activities from human heart and the sequence similarities between these two enzymes (23,24). GST is known to be abundant in placenta.…”
Section: Mechanism O F Ethanol Teratogenesismentioning
confidence: 99%
“…In addition, another GST3, the major GST isoenzyme expressed in placenta, FAEE synthase isoenzyme purified from human and the GST isoenzyme with the closest N-terminal'semyocardium also displayed GST activity [2]. These quence to that reported for the rnyocardial FAEE synresults suggested that some of the FAEE synthase isoenthase [l].…”
Section: Introductionmentioning
confidence: 83%